Research on Cooperative Control of the Hydraulic System of Multiple Intelligent Vehicles Combined Transportation - Jianjun Wang; Jingyi Zhao (Journal of Advanced Transportation)
The multi-vehicle combined transportation of large-scale equipment or goods is studied, and various combined transportation modes are obtained. The research on four-vehicle combined transportation is studied, the four transport vehicles must ensure synchronization in the process of running, and the steering must be coordinated, otherwise major accidents may occur. Aiming at the stability control of multi-vehicle running synchronization, the system transfer function of pump-controlled motor in driving system is established, and the PID control is added. The simulation results show that adding the PID control algorithm can improve the speed stability of the transport vehicle. And the geometric model of the steering mechanism is established, the functional relationship between the steering angle and the stroke of the steering cylinder is obtained, and the relationship between the electric signal of proportional valve and the steering angle is deduced. On this basis, the coordinated control system of four-vehicle running synchronization and steering coordination based on CAN (controller area network) bus is designed. The master-slave synchronization control strategy and the PID control are applied to the four-vehicle combined transportation. According to the data collected from the test, it is proved that the control strategy fully meets the transportation requirements, and can provide theoretical basis and design method reference for the safe and reliable combined transportation of various types of transport vehicles.